Penerapan Metode Jigsaw untuk Peningkatan Pemahaman Konsep Multikultural Matapelajaran Pengetahuan Sosial SD - Ahmad Samawi; Ana Nirawati; Hartini Hartini (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
This classroom action research examines the implementation of jigsaw methods in improving students' understanding of multicultural concepts in social science subjects. Carried out in three cycles of action, this study involved 46 fourth-grade students. The data collected through observation, documentation, and interviews were descriptively analyzed. The results show that jigsaw methods improved the students' understanding of multicultural concepts in social science.